Native characterization of nucleic acid motif thermodynamics via non-covalent catalysis - Chunyan Wang (Nature Portfolio, 2016)
DNA hybridisation thermodynamics parameters underlie rational design of oligonucleotides for diagnostics and nanotechnology. Here, the authors present an accurate method to measure the free energy of a given DNA structure at specific temperature and buffer conditions.